Glittre-Activities daily living test: physiological response in heart failure patients - Almeida, José Miguel Lopes Peixoto de (2019)
Background: Functional capacity and quality of life are measures of the heart failure (HF) patient’s health status and can demonstrate the impact of the disease on the ability to perform activities of daily living (ADL´s). The Glittre-ADL (TGlittre) test is supposed to evaluate patient´s functional capacity and their ability to perform activities of daily life. The physiological requirements of this test in HF patients are still unknown. Aim(s): Analyze and compare the cardiac, ventilatory and metabolic performance of the TGlittre, 6 minute walk test (6MWT) and cardiopulmonary exercise test (CPET) in patients with HF. Methods: A prospective cross-sectional study with 11 patients of both genders (median age of 65) with HF (median left ventricle ejection fraction of 40%) underwent anthropometric and lung function assessments and were submitted to a CPET. In separate day, with a maximum of 10 days apart, patients performed the TGlittre and 6MWT. Results: Baseline cardiopulmonary variables were similar between TGlittre and 6MWT (p>0,05). TGlittre induce significantly higher VE, VE/VO2, RER, HR and VE/MVV (p<0,05) compared to 6MWT. The other physiological variables were similar at the end of both tests. TGlittre showed a significant correlation with 6MWT distance (r=-0,64; p=0,04). In the final oxygen consumption (VO2), TGlittre showed a significant correlation with CPET (r=0,72; p=0,01) and 6MWT (r=0,67; p=0,02). TGlittre showed submaximal characteristics when compared with the CPET. Conclusion: TGlittre induce higher ventilatory and cardiovascular responses than the 6MWT, with similar metabolic adjustments.